Journal of Nigerian Society of Physical Sciences (Department of Physics, 2019)
"Offers an exciting publication outlet for Physical Science reports. It covers all areas of Theoretical Physics, Geophysical & Atmospheric Physics, Radiation & Medical Physics, Solid State Physics, Astrophysics & Cosmology, Environmental Chemistry, Physical Chemistry, Organic & Inorganic Chemistry, Artificial Intelligence, Computer Architecture & Engineering, Database Management Systems, Human-Computer Interaction, Operating Systems & Networking, Pure Mathematics, Number theory, Applied mathematics, Mathematical Finance, Numerical Analysis & Scientific Computing, Topology & Differential Geometry, Biostatistics & Data Science Decision Analysis and Support, Econometric Modelling, Planetary Exploration and Exoplanets".